Mechatronics in Sustainable Mobility: Two Electric Vehicle Applications - Longo, Stefano; Auger, Daniel J.; Assadian, Francis (Greenleaf, 2014)
In this paper, we ﬁrst review the role that mechatronics and advanced control have in modern road vehicles, in particular their present and potential impact on sustainable mobility. We then illustrate this with two research examples. Firstly, we show how electronic science, control system techniques and computing manifest themselves in the design of an advanced battery management algorithm designed to estimate two unmeasurable but vital quantities, State of Charge (SoC) and State of Health (SoH): this allows better utilisation of battery capacity, with scope for advanced prognostics and diagnostics. Secondly, we show how multi-domain modelling integrating mechanical science and electronic science can be used to express component ageing as part of a set of vehicle-level performance objectives and used to explore the trade-offs between conﬂicting requirements, aiding sensible design choices.
© The Author